Caesarius of Arles’ Sermons, Martin of Braga’s De correctione rusticorum, and Venantius Fortunatus’ Poems V. 1 and 2 - Ferreiro, Alberto (Augustinianum, 2024)
This study evaluates the evidence that we have that Caesarius of Arles, Martin of Braga, and Venantius Fortunatus knew each other perhaps even beyond epistolary correspondence. Some scholars think so even thought in some aspects the evidence is scant. The question is considered within the broader context of commercial, diplomatic, and ecclesial links between Gallia and Suevic Gallaecia in the Northwest of the Iberian Peninsula of which there is absolutely no doubt. The focus of our evidence is the sermons of Caesarius of Arles that may have influenced Martin’s sermon against paganism, De correctione rusticorum and Poems V.1 and 2 dedicated to Martin of Braga by Venantius Fortunatus.